Failure Analysis and Prevention 2017
DOI: 10.5772/intechopen.69440
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Mode Delamination Failures of Quasi-Isotropic Quasi- Homogeneous Carbon/Epoxy Laminated Composite

Abstract: This chapter characterised the delamination behaviour of a quasi-isotropic quasi-homogeneous (QIQH) multidirectional carbon/epoxy-laminated composite. The delaminated surface constituted of 45 //0 layers. Specimens were tested using mode I double cantilever beam (DCB), mode II end-notched flexure (ENF) and mixed-mode I+II mixed-mode flexure (MMF) tests at constant crosshead speed of 1 mm/min. Results showed that the fracture toughness increased with the mode II component. Specifically, the mode I, mode II and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…In addition, significant shear cusps were also noticed, which indicated shear mode of delamination. Similar observation was reported in [16,34]. Davidson et al [13] described the repeated pattern of shear cusps as hackles, which was common in mode II delamination of brittle matrix composites.…”
Section: Morphology Studiessupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, significant shear cusps were also noticed, which indicated shear mode of delamination. Similar observation was reported in [16,34]. Davidson et al [13] described the repeated pattern of shear cusps as hackles, which was common in mode II delamination of brittle matrix composites.…”
Section: Morphology Studiessupporting
confidence: 72%
“…The maximum value of the R-curve was approximately 400 N/m −1 , which corresponded to 220% of augmentation. R-curve was about 80–100% in vacuum bagging fabricated and multidirectional (0//45) T600S/R368-1 carbon epoxy composite [16, 34]. Besides, it was about 25% only in the E-glass/bismaleimide composite that was immersed in sea water at 50°C [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 compares the interlaminar fracture toughness of the flax/epoxy composite with some synthetic fibre composites reported in the literature [6, 22, 25, 26, 32-35]. Up to the authors’ knowledge, there was no mixed-mode delamination on flax/epoxy composites reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…However, the complete damage ( D = 1) for all ten elements happens at the same time (around t = 210 s) immediately after the peak load is attained (at t = 209 s). The total damage ( D = 1) of the elements all occurring at the same instant leads to the sudden drop in the sustained load, implying an unstable crack propagation which is common in an ENF test [ 2 , 21 , 45 , 46 , 47 ]. This phenomenon is known as the crack jump [ 2 ].…”
Section: Numerical Modelingmentioning
confidence: 99%